TRAINING THE DOG TO BE FAITHFUL IN LASSE HALLSTROM'S "HACHIKO DOG STORY" MOVIE (2009): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - ISDIYATI, NUR (2011)
This study investigates "How is Parker training the dog to be faithful reflected in Hachiko Dog's Story Movie?" viewed from individual psychological approach. Therefore, this research is aimed at analyzing the structure elements of Hachiko Dog's Story movie 2009 and describing the struggle of Parker Wilson in training Hachi to be faithful based on individual psychological approach. This research is qualitative research. The object of the study is Hachiko Dog's Story movie directed by Lasse Hallstrom and publishing by Sony Pictures Entertainment in 2009. The primary data source is Hachiko Dog's Story movie itself and the secondary data sources are the other sources related to the movie. The technique used in collecting data is the library research. The technique of data analysis is descriptive analysis. Based on analysis, there are two conclusions. First based on structural analysis, Lasse Hallstrom wants to deliver a moral message of loving someone forever. Secondly, based on the individual psychological analysis, it shows that in the individual psychological study, integrity makes Parker to get anything. His inferior felling makes his feeling weak but he can get his spirit again and he always tries to be the best in his life. Love and patience are the key to get happiness.